2012
DOI: 10.1007/s11033-012-2234-3
|View full text |Cite
|
Sign up to set email alerts
|

GPX1 gene Pro200Leu polymorphism, erythrocyte GPX activity, and cancer risk

Abstract: A meta-analysis was conducted to assess the effect of glutathione peroxidase1 (GPX1) gene Pro200Leu (rs1050450) polymorphism on cancer risk. A comprehensive search was performed to identify all studies on the association of GPX1 gene Pro200Leu polymorphism with cancer risk. The fixed or random effect pooled measure was selected based on homogeneity test among studies. Heterogeneity among studies was evaluated using the I (2). Potential sources of between-study heterogeneity were explored by met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
1
16
0
1
Order By: Relevance
“…Increased understanding of the mechanisms that cells use to respond to mitochondrial oxidative stress in vivo is less thoroughly investigated to date and may be relevant in understanding the pathogenesis of complex disease, particularly as a reduced capacity to mount and antioxidant response is linked with a number of disease states [55, 56, 58, 59], as well as the ageing process [84]. …”
Section: Mitochondrial Stress Signalsmentioning
confidence: 99%
“…Increased understanding of the mechanisms that cells use to respond to mitochondrial oxidative stress in vivo is less thoroughly investigated to date and may be relevant in understanding the pathogenesis of complex disease, particularly as a reduced capacity to mount and antioxidant response is linked with a number of disease states [55, 56, 58, 59], as well as the ageing process [84]. …”
Section: Mitochondrial Stress Signalsmentioning
confidence: 99%
“…The results of a meta‐analysis performed by Men et al showed the significant correlation of the rs1050450 polymorphism with an increased risk of bladder cancer, while there was no significant association for prostate cancer . In addition, the meta‐analysis by Chen et al indicated the correlation of the individuals with variant Leu allele of rs1050450 with an increased cancer risk in dominant genetic model; however, Hong et al's meta‐analysis results showed no association of GPX1 gene rs1050450 polymorphism with cancer risk in any of dominant and recessive models . Recent study by Yang et al showed the effect of rs1050450 on breast cancer risk, while Nikic et al and Zhang et al showed no significant association between rs1050450 polymorphism and metastatic urothelial bladder and Gastric cancers, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…GPX1 is cytosolic and produced in all tissues. The SNP rs1050450 (or GPX1 Pro198Leu) has been studied extensively in human disease and has already been linked to cancer risk [33], and oxidative stress related diseases [34]. The Leu198 variant results in a 10% reduced enzyme activity compared with the Pro198 variant [35], interfering with the overall capacity to respond to oxidative damage [34].…”
Section: Discussionmentioning
confidence: 99%